A survey of physicians' experience and awareness of institutional provisions designed to foster patient engagement in KSA. Issue 3 (June 2018) - Shahahmad, Bayan S.; Khan, Anas A.; Batais, Mohammed A.; Gaumer, Gary L.
الملخص: أهداف البحث: للحصول على تصورات الأطباء عن خبراتهم ووعيهم حول الأحكام المؤسسية التي يمكن أن تعزز مشاركة المريض في المملكة العربية السعودية. طرق البحث: في إبريل٢٠١٧، تم عمل استطلاع عبر الإنترنت عن طريق توزيع استبانة عبر نموذج مستند جوجل للأطباء في المملكة العربية السعودية. يحتوي المستند أسئلة حول خبرة ووعي الأطباء للأحكام المؤسسية من الموارد والدعم. النتائج: استجاب للاستطلاع ٣٢٥ طبيبا. وأوضحت النتائج أن ١٨.٥٪ منهم يرون أن مؤسساتهم تسمح بجدولة المواعيد عن طريق الإنترنت، و٨.٩٪ تسمح بالتواصل بين المرضى والأطباء عبر البريد الإلكتروني، و٢٤٪ تسمح لوصول المرضى للسجلات الصحية ونتائج التحاليل عبر الإنترنت، و٥٥.٧٪ تسمح بتوفير البرامج التعليمية متعددة الوسائط، و٧٤.٨٪ تسمح بصنع القرار-المشترك بين الأطباء والمرضى. كما ذكر ٣٤.٥٪ فقط من المستجيبين أن مؤسساتهم تقوم بتوفير زيارات منزلية للمرضى ذوي الخطورة العالية. يرى ستة من ١٠ مستجيبين أن هذه الأحكام سيكون لها تأثير إيجابي ونتيجة لهم وأيضا لمرضاهم. الاستنتاجات: يعي الأطباء ويقيمون الأحكام التي تعزز مشاركة المريض. ولكن العديد من المؤسسات لا تدعم وتمارس هذه الأحكام التي تعزز مشاركة المريض. الأطباء الذكور ذوي الخبرة الأطول من الممارسة وأولئك الذين يشغلون مناصب إدارية عليا هم أكثر من يقدم الدعم، ويقدر أهمية تعزيز مشاركة المريض في ممارستهم. Abstract: Objectives: To survey physicians' perceptions of their experience and awareness of institutional provisions that can potentially foster patient engagement (PE) in KSA. Methods: In April 2017, an online survey was distributed to clinicians in KSA using Google Forms. The instrument contained questions about the physicians' awareness and experience of their institutions' provision of resources and support. Results: Three hundred and twenty-five clinicians responded to the survey The results showed that 18.5% claimed that their institutions allowed online scheduling of appointments; 8.9% reported the institutions permitted contact between patients and physicians through email; 24.0% reported they provided patients with online access to health records and test results; 55.7% claimed they provided educational multimedia programming; and 74.8% confirmed they encouraged joint decision-making between physicians and patients. Only 34.5% of respondents claimed their institutions provided home visits for high-risk patients. Six of 10 respondents thought that such provisions would have positive outcomes for them and for their patients. Conclusions: Clinicians are aware of and value provisions that foster PE. However, several institutions in KSA do not support or have provisions in place to foster PE. Male clinicians with longer durations of practice and those with higher administrative positions are more likely to value the importance of PE and support and use it in their practice.